High quantum efficiency ruthenium coordination complex photosensitizer for improved radiation-activated Photodynamic Therapy - Azad, Abul Kalam; Lilge, Lothar; Usmani, Nawaid H.; Lewis, John D.; Cole, Houston D.; Cameron, Colin G.; McFarland, Sherri A.; Dinakaran, Deepak; Moore, Ronald B. (Frontiers in Oncology, 2023)
Traditional external light-based Photodynamic Therapy (PDT)'s application is limited to the surface and minimal thickness tumors because of the inefficiency of light in penetrating deep-seated tumors. To address this, the emerging field of radiationactivated PDT (radioPDT) uses X-rays to trigger photosensitizer-containing nanoparticles (NPs). A key consideration in radioPDT is the energy transfer efficiency from X-rays to the photosensitizer for ultimately generating the phototoxic reactive oxygen species (ROS). In this study, we developed a new variant of pegylated poly-lactic-co-glycolic (PEG-PLGA) encapsulated nanoscintillators (NSCs) along with a new, highly efficient ruthenium-based photosensitizer (Ru/radioPDT). Characterization of this NP via transmission electron microscopy, dynamic light scattering, UV-Vis spectroscopy, and inductively coupled plasma mass-spectroscopy showed an NP size of 120 nm, polydispersity index (PDI) of less than 0.25, high NSCs loading efficiency over 90% and in vitro accumulation within the cytosolic structure of endoplasmic reticulum and lysosome. The therapeutic efficacy of Ru/radioPDT was determined using PC3 cell viability and clonogenic assays. Ru/radioPDT exhibited minimal cell toxicity until activated by radiation to induce significant cancer cell kill over radiation alone. Compared to protoporphyrin IX-mediated radioPDT (PPIX/radioPDT), Ru/radioPDT showed higher capacity for singlet oxygen generation, maintaining a comparable cytotoxic effect on PC3 cells.